Research lab on 3D bioprinting of Zhejiang University - Gao, L; Zhang, B; Ma, L; Luo, Y; Xue, Q; Cui, Z; Yang, H (Springer, 2018)
The Research Lab on 3D Bioprinting of Zhejiang University focuses on developing innovative 3D bioprinting equipment and technology for healthcare and biomedical applications, since founded in 2017. To further enhance the international collaboration, a joint international research lab on 3D bioprinting of Zhejiang University and University of Oxford was set up. The lab is based on the State Key Laboratory of Fluid Power and Mechatronic Systems and the Oxford Centre for Tissue Engineering and Bioprocessing. The aim of the lab is to establish a world class research and development platform on 3D bioprinting. The lab has extensive and close collaborations with University of Oxford, University College London and multidisciplinary partners of Zhejiang University.